Ternary sulfide as well as preparation method and application thereof
The ternary sulfide CdIn2S4 nanospheres prepared by a one-step hydrothermal method, as the negative electrode material of sodium ion battery, solve the problems of poor electrochemical performance and volume expansion of sodium ion battery, and achieve the improvement of high capacity, long life and high rate performance.
Patent Information
- Application Number
- CN202411897786.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
Due to the large sodium ion radius, sodium ion batteries are difficult to embed into graphite lattices, resulting in poor electrochemical performance, poor circulation performance and volume expansion problems, which limit their practical application.
The ternary sulfide CdIn2S4 was prepared by a one-step hydrothermal method. By reacting CdCl2, InCl3 and TAA in ammonia water, nanospheres with hollow structures were formed as the negative electrode material for sodium ion batteries.
It significantly improves the theoretical capacity and actual capacity of the negative electrode material of sodium ion battery, improves cycle stability and life, adapts to volume changes during charging and discharging, and improves the high-rate performance of the battery.
Smart Images

Figure CN119683685A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion battery materials, and in particular relates to a ternary sulfide, a preparation method and application thereof. Background Art
[0002] Due to urgent issues such as resource scarcity, climate change and accelerated urbanization, clean and renewable energy technologies have received widespread attention. The strategic goals of "carbon peak" and "carbon neutrality" have pointed out the direction for China's future green energy development. The development and utilization of clean energy has become increasingly urgent, and traditional lithium-ion batteries based on graphite negative electrodes have been unable to meet the needs of the rapid development of electric vehicles and smart grid technologies.
[0003] Sodium-ion batteries have attracted widespread attention due to their low self-discharge, abundant sodium reserves and low cost. Sodium-ion batteries have similar physical and chemical mechanisms to lithium-ion batteries and can be a perfect substitute for lithium-ion batteries. However, since the radius of sodium ions is larger than that of lithium ions, it is difficult to embed into the graphite lattice during the sodium insertion / deintercalation process, so traditional commercial graphite negative electrodes exhibit poor electrochemical performance when applied to sodium-ion batteries. In addition, since the mass of sodium ions is larger than that of lithium ions, the transmission of sodium ions is hindered, resulting in large volume changes and slow diffusion kinetics, which limits the practical application of sodium-ion batteries. Summary of the invention
[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to solve at least one technical problem existing in the above-mentioned sodium ion battery, and to propose a ternary sulfide with long life, high specific capacity and high rate performance, and its preparation method and application.
[0005] In order to solve the technical problem, the technical solution adopted by the present invention is:
[0006] On one hand, the present invention provides a method for preparing a ternary sulfide, comprising the following steps: adding CdCl2, InCl3, and TAA to deionized water, then adding ammonia water, and after magnetic stirring, transferring the mixed solution to a polytetrafluoroethylene reactor substrate, reacting at 100-180°C, obtaining a mixed substance, centrifuging, washing, drying, and solid grinding to obtain a ternary sulfide.
[0007] Preferably, in the mixed solution, c(Cd 2+ ): c(In 3+ ) is selected from any value among 1-5:1-2.
[0008] Preferably, in the mixed solution, c(In 3+ ):c(TAA) is selected from any value in 2:1-7.
[0009] Preferably, in the mixed solution, c(Cd 2+ ):c(TAA) is selected from any value in the range of 1:3-9.
[0010] Preferably, the molar ratio of the CdCl2, the InCl3, and the TAA is 1:2:5.
[0011] Preferably, the total molar amount of the CdCl2, the InCl3, and the TAA is 8 mmol, and the volume of the ammonia water is selected from any value between 0.4 and 1.4 mL.
[0012] Preferably, the mixed solution is transferred to a polytetrafluoroethylene reactor substrate and reacted at 100-180° C. for 8-24 hours.
[0013] Preferably, after obtaining the mixed substance, it is centrifuged through a centrifuge, washed repeatedly with water and ethanol to remove impurities, and finally dried in an oven overnight, and the solid is ground to obtain the ternary sulfide.
[0014] Another aspect of the present invention provides a ternary sulfide prepared by the method for preparing a ternary sulfide described in any of the above technical solutions, wherein the ternary sulfide is a nanosphere with a hollow structure.
[0015] The present invention also provides the use of the ternary sulfide described in the above technical solution in a sodium ion battery, wherein the ternary sulfide is used as a negative electrode material in the sodium ion battery.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention provides a method for preparing a ternary sulfide. The ternary sulfide with excellent performance can be obtained by a one-step hydrothermal method. The preparation is simple and convenient, which is conducive to large-scale industrial batch production.
[0018] The present invention provides a ternary sulfide, which can effectively solve the problems of poor cycle performance and great volume expansion of negative electrode materials of sodium ion batteries, and improve the cycle stability of the battery;
[0019] The present invention also provides an application of a ternary sulfide in a sodium ion battery. The ternary metal sulfide can significantly improve the theoretical capacity of the negative electrode material of the sodium ion battery, which is beneficial to improving the actual capacity of the battery. The ternary metal sulfide has a hollow nanosphere structure and can well adapt to the volume change problem generated during the charging and discharging process, thereby improving the cycle life of the battery. At the same time, more active sites of the active material are exposed, thereby improving the capacity of the battery. As a negative electrode material for a sodium ion battery, the ternary metal sulfide has the advantages of long life, high specific capacity, and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1XRD image of hollow CdIn2S4 nanospheres provided in an embodiment of the present invention;
[0021] Figure 2 The SEM image of the hollow CdIn2S4 nanospheres provided in the embodiment of the present invention;
[0022] Figure 3 TEM image of hollow CdIn2S4 nanospheres provided by an embodiment of the present invention;
[0023] Figure 4 The hollow CdIn2S4 nanospheres provided in the embodiment of the present invention are -1 Cycle performance;
[0024] Figure 5 The rate performance of the hollow CdIn2S4 nanospheres provided in the embodiments of the present invention. DETAILED DESCRIPTION
[0025] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.
[0026] In one aspect, the present invention provides a method for preparing a ternary sulfide, comprising the following steps:
[0027] (Cadmium chloride), InCl3 (indium chloride), TAA (thioacetamide) are added to deionized water, followed by ammonia water. After magnetic stirring, the mixture is transferred to a polytetrafluoroethylene reactor substrate and reacted at 100-180°C. After the mixture is obtained, it is centrifuged, washed, dried, and solid ground to obtain the ternary sulfide CdIn2S4.
[0028] It should be noted that conversion metal sulfides have become a research hotspot for negative electrode materials of sodium ion batteries due to their high theoretical capacity and abundant earth resources. In addition, binary metal sulfides have been reported more frequently, but ternary metal sulfides have rarely been reported, and there is no related process technology for preparing negative electrode materials for sodium ion batteries by using a simple hydrothermal sulfidation method to obtain ternary metal sulfides in one step. The above-mentioned method for preparing ternary sulfides can obtain ternary sulfides with excellent performance through a one-step hydrothermal method. The preparation is simple and convenient, which is conducive to large-scale industrial batch production. It is understandable that the reaction temperature can also be 120°C, 140°C, 160°C and any point value within the range.
[0029] In a preferred embodiment, in the mixed solution, c(Cd 2+): c(In 3+ ) is selected from any value in 1-5:1-2. It is understood that c(Cd 2+ ): c(In 3+ ) can also be 1:1, 1:2, 3:1, 5:1.
[0030] In a preferred embodiment, in the mixed solution, c(In 3+ ):c(TAA) is selected from any value in the range of 2:1-7. It is understood that c(In 3+ ):c(TAA) can also be 2:1, 2:3, 2:5, 2:7.
[0031] In a preferred embodiment, in the mixed solution, c(Cd 2+ ):c(TAA) is selected from any value in the range of 1:3-9. It is understood that c(Cd 2+ ):c(TAA) can also be 1:3, 1:4, 1:5, 1:7, 1:9.
[0032] In a preferred embodiment, the molar ratio of the CdCl2, the InCl3, and the TAA is 1:2:5.
[0033] In a preferred embodiment, the total molar amount of the CdCl2, the InCl3, and the TAA is 8 mmol, and the volume of the ammonia water is selected from any value in the range of 0.4-1.4 mL. It is understood that the volume of the ammonia water can also be 0.4, 0.6, 0.8, 1.0, 1.2, 1.4 mL and any point value in the range.
[0034] In a preferred embodiment, the mixed solution is transferred to a polytetrafluoroethylene reactor substrate and reacted at 100-180° C. for 8-24 hours. It is understood that the above reaction time can also be 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours and any point value within the range.
[0035] In a preferred embodiment, the mixed substance is centrifuged, washed repeatedly with water and ethanol to remove impurities, and finally dried in an oven overnight, and the solid is ground to obtain the ternary sulfide.
[0036] Another aspect of the present invention provides a ternary sulfide prepared by the method for preparing a ternary sulfide according to any of the above technical solutions, wherein the ternary sulfide is a nanosphere with a hollow structure. The ternary sulfide can effectively solve the problems of poor cycle performance and large volume expansion of negative electrode materials of sodium ion batteries, and improve the cycle stability of the battery.
[0037] The present invention also provides the application of the ternary sulfide described in the above technical solution in a sodium ion battery, wherein the ternary sulfide is used as a negative electrode material in the sodium ion battery. The ternary metal sulfide can significantly improve the theoretical capacity of the negative electrode material of the sodium ion battery, which is beneficial to improving the actual capacity of the battery. It has a hollow nanosphere structure, which can well adapt to the volume change problem generated during the charging and discharging process, thereby improving the cycle life of the battery, and at the same time, more active sites of the active material are exposed, thereby improving the capacity of the battery. As a negative electrode material for a sodium ion battery, it has the advantages of long life, high specific capacity, and high rate performance.
[0038] In order to more clearly and in detail introduce the ternary sulfide provided by the embodiments of the present invention, its preparation method and application, the following will be described in conjunction with specific embodiments.
[0039] Example 1
[0040] 1mmol cadmium chloride (CdCl2), 2mmol indium chloride (InCl3), and 5mmol thioacetamide (TAA) were added to 30mL deionized water, followed by 1.2mL ammonia water. After magnetic stirring, the mixture was transferred to a polytetrafluoroethylene reactor substrate and reacted at 120°C for 12h. The obtained mixed substance was centrifuged, repeatedly washed with water and ethanol to remove impurities, and finally the product was dried in an oven overnight and solid ground to obtain a ternary metal sulfide.
[0041] Example 2
[0042] 1mmol cadmium chloride (CdCl2), 2mmol indium chloride (InCl3), and 5mmol thioacetamide (TAA) were added to 30mL deionized water, followed by 1.4mL ammonia water. After magnetic stirring, the mixture was transferred to a polytetrafluoroethylene reactor substrate and reacted at 120°C for 12h. The obtained mixed substance was centrifuged, repeatedly washed with water and ethanol to remove impurities, and finally the product was dried in an oven overnight and solid ground to obtain a ternary metal sulfide.
[0043] Example 3
[0044] 1mmol cadmium chloride (CdCl2), 2mmol indium chloride (InCl3), and 5mmol thioacetamide (TAA) were added to 30mL deionized water, followed by 1.4mL ammonia water. After magnetic stirring, the mixture was transferred to a polytetrafluoroethylene reactor substrate and reacted at 100°C for 12h. The obtained mixed substance was centrifuged, repeatedly washed with water and ethanol to remove impurities, and finally the product was dried in an oven overnight and solid ground to obtain a ternary metal sulfide.
[0045] Example 4
[0046] 1mmol cadmium chloride (CdCl2), 2mmol indium chloride (InCl3), and 5mmol thioacetamide (TAA) were added to 30mL deionized water, followed by 1.4mL ammonia water. After magnetic stirring, the mixture was transferred to a polytetrafluoroethylene reactor substrate and reacted at 120°C for 24h. The obtained mixed substance was centrifuged, repeatedly washed with water and ethanol to remove impurities, and finally the product was dried in an oven overnight and solid ground to obtain a ternary metal sulfide.
[0047] Example 5
[0048] 1mmol cadmium chloride (CdCl2), 2mmol indium chloride (InCl3), and 5mmol thioacetamide (TAA) were added to 30mL deionized water, followed by 1.0mL ammonia water. After magnetic stirring, the mixture was transferred to a polytetrafluoroethylene reactor substrate and reacted at 120°C for 24h. The obtained mixed substance was centrifuged, repeatedly washed with water and ethanol to remove impurities, and finally the product was dried in an oven overnight and solid ground to obtain a ternary metal sulfide.
[0049] Comparative Example 1
[0050] 1mmol cadmium chloride (CdCl2), 1mmol indium chloride (InCl3), and 2mmol thioacetamide (TAA) are added to 30mL deionized water, followed by 1.2mL ammonia water. After magnetic stirring, the mixture is transferred to a polytetrafluoroethylene reactor substrate and reacted at 200°C for 12h. The obtained mixed substance is centrifuged, repeatedly washed with water and ethanol to remove impurities, and finally the product is dried in an oven overnight and solid ground to obtain a ternary metal sulfide (non-pure phase) with impurities.
[0051] Comparative Example 2
[0052] 1mmol cadmium chloride (CdCl2), 2mmol indium chloride (InCl3), and 5mmol thioacetamide (TAA) are added to 30mL deionized water, followed by 1.8mL ammonia water. After magnetic stirring, the mixture is transferred to a polytetrafluoroethylene reactor substrate and reacted at 120°C for 12h. The obtained mixed substance is centrifuged, repeatedly washed with water and ethanol to remove impurities, and finally the product is dried in an oven overnight and solid ground to obtain a ternary metal sulfide (non-pure phase) with impurities.
[0053] Performance Testing
[0054] The ternary metal sulfide prepared in Example 1 was characterized and its performance tested. The results are as follows: Figure 1-5 shown.
[0055] Depend on Figure 1It can be found that the prepared ternary metal sulfide corresponds to cubic CdIn2S4 (PDF#27-0060);
[0056] Depend on Figure 2 It can be found that the surface morphology of the prepared ternary metal sulfide CdIn2S4 is mainly nanosphere morphology;
[0057] Depend on Figure 3 It can be found that the prepared ternary metal sulfide CdIn2S4 has a hollow nanosphere structure;
[0058] Depend on Figure 4 It can be found that when CdIn2S4 hollow nanospheres are used as the negative electrode material of sodium ion batteries, at 1000mA g -1 After 300 cycles at the same current density, it can still maintain 318.6 mAh g -1 The reversible specific capacity;
[0059] Depend on Figure 5 It can be found that when CdIn2S4 hollow nanospheres are used as the negative electrode material of sodium ion batteries, their rate performance is tested at different current densities. They can provide 313.5, 286.1, 264.3, 242.6, 222.7, 196.2, 161.1 mAh g at current densities of 200, 500, 1000, 2000, 3000, 5000 and 8000, respectively. -1 The high discharge specific capacity, and when the current density returns to the initial current, its capacity can also return to the initial value.
Claims
1. A method for preparing a ternary sulfide, characterized in that: The following steps are involved: CdCl2, InCl3, and TAA are added to deionized water, followed by ammonia water. After being magnetically stirred to be uniform, the mixed solution is transferred to a polytetrafluoroethylene reactor substrate and reacted at 100-180° C. After the mixed substance is obtained, it is centrifuged, washed, dried, and solid ground to obtain a ternary sulfide.
2. The method for preparing ternary sulfide according to claim 1, characterized in that: In the mixed solution, c(Cd 2+ ): c(In 3+ ) is selected from any value among 1-5:1-2.
3. The method for preparing the ternary sulfide according to claim 2, characterized in that: In the mixed solution, c(In 3+ ):c(TAA) is selected from any value in 2:1-7.
4. The method for preparing the ternary sulfide according to claim 3, characterized in that: In the mixed solution, c(Cd 2+ ):c(TAA) is selected from any value in the range of 1:3-9.
5. The method for preparing ternary sulfide according to claim 1, characterized in that: The molar ratio of the CdCl2, the InCl3, and the TAA is 1:2:
5.
6. The method for preparing ternary sulfide according to claim 1, characterized in that: The total molar amount of the CdCl2, the InCl3, and the TAA is 8 mmol, and the volume of the ammonia water is selected from any value between 0.4 and 1.4 mL.
7. The method for preparing ternary sulfide according to claim 1, characterized in that: The mixed solution was transferred to a polytetrafluoroethylene reactor substrate and reacted at 100-180°C for 8-24 hours.
8. The method for preparing ternary sulfide according to claim 1, characterized in that: After the mixed substance is obtained, it is centrifuged, washed repeatedly with water and ethanol to remove impurities, and finally dried in an oven overnight, and the solid is ground to obtain the ternary sulfide.
9. The ternary sulfide prepared by the method for preparing a ternary sulfide according to any one of claims 1 to 8, characterized in that: The ternary sulfide is a nanosphere with a hollow structure.
10. The use of the ternary sulfide in a sodium ion battery according to claim 9, characterized in that: The ternary sulfide is used as a negative electrode material in the sodium ion battery.